Assessments of Climate Literacy and Climate Change Awareness - Cintami, Cincin; Rachman, Indriyani; Permanasari, Anna; Matsumoto, Toru (Universitas Diponegoro, 2026)
Climate change has become a serious threat to all humans, with impacts already being felt throughout the planet. One effort in climate change education is to improve students' climate literacy and climate change awareness. This study aimed to measure climate literacy and climate change awareness among vocational high school students and analyze the relationship between aspects of these two variables. A questionnaire with a 5-point Likert scale was used, and the data were processed using descriptive statistics and Pearson ’scorrelation analysis. The results from 295 respondents showed that the average climate literacy was in the high category (3.50), while climate change awareness was in the medium category (3.40). However, both showed significant gaps in each aspect. The results of the correlation analysis showed a significant relationship between attitudes and behavior, both in climate literacy (r = 0.323) and climate change awareness (r = 0.142). Climate change education not only conveys information in the form of knowledge but also includes efforts to strengthen attitudes that can encourage sustainable climate-friendly behavior. The results of this study will serve as the basis for developing climate change teaching materials in vocational high schools to improve students' climate literacy and climate change awareness.